Safety knowledge as predictor of accident prevention and crisis management among health and industrial social workers in southwest Nigeria (2017)
"Safety consciousness is an everyday affair that is closely knitted with security. Safety consciousness which is a way of accident prevention couple with crisis management has become a challenge in the workplace. The absence of knowledge of safety on the part of Social workers intervention in accident prevention and crisis management has become challenging in different ways to the extent of affecting individuals, families, organizations and communities. To this end this study looked at safety knowledge as predictor of accident prevention and crisis management among health and industrial social workers in South-West Nigeria. The study adopts the descriptive survey research design with the population consisting of health social workers in public hospitals and industrial social workers in selected manufacturing firms in the South West Nigeria. Random sampling was used to select three states, Oyo, Lagos and Ogun States, out of the six states in the South West. The population was clustered into health and industrial sectors. Purposive sampling technique was used to select forty respondents from each stratum thereby making a total of two hundred and forty respondents. A self-developed questionnaire tagged “Safety Knowledge, Accident prevention and Crisis Management Questionnaire- SKAPCMQ” with a reliability coefficient of 0.84 was used for data collection. The instrument was rated on a four-point scale of Strongly Disagree (SD=1), Disagree (D=2), Agree (A=3), Strongly Agree (SA=4). Frequency counts and percentages were used to analyse the demographic characteristics of the respondents while Pearson Product Moment Correlation was used to test the research hypotheses at 0.05 level of significance. Findings from the study showed that health and industrial social workers’ safety knowledge had a significant relationship with accident prevention (r = 0.855, P < 0.05) and that health and industrial social workers’ safety knowledge had a significant relationship with crisis management (r = 0.529, P < 0.05). Based on these findings, it was recommended that employers should provide financial support for in-service training of social workers on crisis and disaster management to improve proficiency of the work force. "